Sources of moral distress for nursing staff providing care to residents with dementia. (October 2017) - Spenceley, Shannon; Witcher, Chad SG; Hagen, Brad; Hall, Barry; Kardolus-Wilson, Arron
The World Health Organization estimates the number of people living with dementia at approximately 35.6 million; they project a doubling of this number by 2030 and tripling by 2050. Although the majority of people living with a dementia live in the community, residential facility care by nursing care providers is a significant component of the dementia journey in most countries. Research has also shown that caring for persons with dementia can be emotionally, physically, and ethically challenging, and that turnover in nursing staff in residential care settings tends to be high. Moral distress has been explored in a variety of settings where nurses provide acute or intensive care. The concept, however, has not previously been explored in residential facility care settings, particularly as related to the care of persons with dementia. In this paper, we explore moral distress in these settings, using Nathaniel's definition of moral distress: the pain or anguish affecting the mind, body, or relationships in response to a situation in which the person is aware of a moral problem, acknowledges moral responsibility, makes a moral judgment about the correct action and yet, as a result of real or perceived constraints, cannot do what is thought to be right. We report findings from a qualitative study of moral distress in a single health region in a Canadian province. Our aim in this paper is to share findings that elucidate the sources of moral distress experienced by nursing care providers in the residential care of people living with dementia.